Deep learning-driven medical image analysis for computational material science applications - Lu, Li; Liang, Mingpei (Frontiers in Materials, 2025)
IntroductionDeep learning has significantly advanced medical image analysis, enabling precise feature extraction and pattern recognition. However, its application in computational material science remains underexplored, despite the increasing need for automated microstructure analysis and defect detection. Traditional image processing methods in material science often rely on handcrafted feature extraction and threshold-based segmentation, which lack adaptability to complex microstructural variations. Conventional machine learning approaches struggle with data heterogeneity and the need for extensive labeled datasets.MethodsTo overcome these limitations, we propose a deep learning-driven framework that integrates convolutional neural networks (CNNs) with transformer-based architectures for enhanced feature representation. Our method incorporates domain-adaptive transfer learning and multi-modal fusion techniques to improve the generalizability of material image analysis.ResultsExperimental evaluations on diverse datasets demonstrate superior performance in segmentation accuracy, defect detection robustness, and computational efficiency compared to traditional methods.DiscussionBy bridging the gap between medical image processing techniques and computational material science, our approach contributes to more effective, automated, and scalable material characterization processes.